2017
DOI: 10.1371/journal.pone.0168840
|View full text |Cite
|
Sign up to set email alerts
|

Wnt Signaling Prevents the Aβ Oligomer-Induced Mitochondrial Permeability Transition Pore Opening Preserving Mitochondrial Structure in Hippocampal Neurons

Abstract: Alzheimer’s disease (AD) is a neurodegenerative disorder mainly known for synaptic impairment and neuronal cell loss, affecting memory processes. Beside these damages, mitochondria have been implicated in the pathogenesis of AD through the induction of the mitochondrial permeability transition pore (mPTP). The mPTP is a non-selective pore that is formed under apoptotic conditions, disturbing mitochondrial structure and thus, neuronal viability. In AD, Aβ oligomers (Aβos) favor the opening of the pore, activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 98 publications
(123 reference statements)
0
33
0
Order By: Relevance
“…At the end, the Wnt blockade will cause the downregulation of the oxidative phosphorylation leading to an altered cellular metabolism. In the context of AD, we showed that Wnt3a treatment prevents mitochondrial damage induced by Ab, possibly by inhibiting opening of the mitochondrial permeability transition pore (mPTP) (Arr azola et al 2017). Wnt signaling also stimulates glucose metabolism in neurons and this could promote the generation of ROS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end, the Wnt blockade will cause the downregulation of the oxidative phosphorylation leading to an altered cellular metabolism. In the context of AD, we showed that Wnt3a treatment prevents mitochondrial damage induced by Ab, possibly by inhibiting opening of the mitochondrial permeability transition pore (mPTP) (Arr azola et al 2017). Wnt signaling also stimulates glucose metabolism in neurons and this could promote the generation of ROS.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of Ab to reduce cellular ATP production in vitro was blocked by Wnt3a treatment and this protective effect was abolished by an ATP synthase inhibitor. This suggests that the major deleterious effects of Ab are due, at least in part, to its effect on mitochondrial energy metabolism and that Wnt signaling exerts its neuroprotective role by restoring mitochondrial function in neurons (Arr azola et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, APC and IPC do not facilitate the binding of phosphor-Ser9-GSK-3β to VDAC or CyP-D [52]. GSK-3β is a key factor in Wnt signaling, which has been reported to regulate the activity of mPTP [53]. Bcl-2 is the target gene of Wnt signaling to participate in the stabilization of mitochondria against Aβ damage.…”
Section: Gsk-3β Regulates Mitochondrial Permeabilitymentioning
confidence: 99%
“…Moreover, it has been found that Aβ can also enter the mitochondria, leading directly to mitochondrial dysfunction and to altered energy metabolism within cells. Along with the reduction of available ATP, altered mitochondria will also increase the production of ROS contributing to increase the brain oxidative status and resulting in the production of additional pro-inflammatory mediators, such as IL-6 [44][45][46][47]. In this regard, once released to the extracellular compartment, ROS can further trigger the inflammatory pathways in the neighboring cells inducing the activation of the NF-kB-dependent pro-inflammatory cascade [20].…”
Section: Mitochondriamentioning
confidence: 99%